Clima escolar e trabalho pedagógico: um estudo sobre a influência dos projetos do contraturno no Ensino Fundamental II - Baptista, Cassia Christina (2018)
There is, for all contexts, a climate that acts on relationships and organizational culture. It is not something that can be seen, but it can be perceived by the actors of a certain place. In this sense, the problem of this research referred to the school climate identified in the periods of time destined to after-school projects and Middle School. The initial assumption was that the climate has strong connection with the learning process of students and should be studied as a way to understand this connection, so that the school community can establish actions to harness the strength of the climate for questions of pedagogical work. The objective was to analyze the relationship of the school climate with the pedagogical work developed in a public school of the Municipality of São Paulo. The references that supported the research were Libâ neo (2015), Lück (2011), Nóvoa (1992), Thurler (2001) and Vinha, Morais and Moro (2017). The research, of qualitative approach, used document analysis, questionnairesand discussion groups as instruments of data collection. The subjects were teachers,management team and students of Middle School of a Municipal School of São Paulo. The method for data analysis followed the assumptions of Prose Analysis (ANDRÉ, 1983). The results obtained showed that the subjects express predominantly positive perceptions of school climate to the Educational Unit, especially in the moments of after-school projects,although the actors recognize that there is much to be done to transform the climate of all spaces. The study also evidenced the need of curricular innovations, methodological innovations and in the practices of school organization and management with regard to the advance of the pedagogical process. Furthermore demonstrated that the projects developed in the after-school are assertive movements for this perspective of intentional intervention of the school climate change and, consequently, of the pedagogical process, considering the fields of interpersonal relationship and school organizations.